Spectral and laser properties of Er3+/Yb3+/Ce3+ tri-doped Ca3NbGa3Si2O14 crystal at 1.55 µm. (1st March 2018) - Gong, Guoliang; Chen, Yujin; Lin, Yanfu; Huang, Jianhua; Gong, Xinghong; Luo, Zundu; Huang, Yidong
Abstract: An Er 3+ /Yb 3+ /Ce 3+ tri-doped Ca3 NbGa3 Si2 O14 (CNGS) crystal was grown by the Czochralski method. Spectral properties of the crystal, including the polarized absorption and fluorescence spectra, the fluorescence decay, as well as the energy transfer efficiency from Yb 3+ to Er 3+ were investigated in detail. End-pumped by a 976 nm diode laser, a 1556 nm continuous-wave laser with a maximum output power of 202 mW and a slope efficiency of 11.4% was achieved in the Er, Yb, Ce:CNGS crystal. The results indicate the Er, Yb, Ce:CNGS crystal is a promising 1.55 µ m laser gain medium.